PENGUJIAN BEBERAPA GALUR UNGGULAN PADI DATARAN TINGGI DI KABUPATEN KERINCI PROPINSI JAMBI - , Endrizal; Bobihoe, Julistia (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2010)
The Performance of Superior Upland Rice Genotype In Kerinci District Jambi Province. The mainobstacle of raising national rice production for the last few years is the difficulty to identify the new high yieldingvariety adaptive to wide growth environment. Development of new high yielding varieties adaptive for specificlocation can be increase rice production and finally can be increase the income of farmer. The yield trials forsome elite lines in different agro ecological ecosystem could identify a new superior genotype adaptive for botha specific location or wide growth environment. The yield trial for upland rice ecosystem was done for two yearsin DS 2006 and 2007. The research was done in Koto Dua Lama Semurup Village, Air Hangat sub distric, Kerincidistric Jambi province. The material consisted of 8 genotypes included check Sarinah. The trials was arranged inrancomized completed block design with 3 replications. The 21 old seedling was planted in 2.5x5 m2 plot sizewith 20 x 20 cm width spacing. The result suggested that RUTTST85B-5-2-2-2-0 was the superior genotype forupland rice in Jambi province. The grain yield of the genotype was 7.19 and 5.8 t/ha or 6.3% and 16% highercompared to that of Sarinah in DS 2006 and 2007 respectively whereas BP1356-1G-KN-4 had the least grain yield(4.87 t/ha dan 4.15 t/ha).The yield component analysis showed the RUTTST85B-5-2-2-2-0 had more productivetiller number, more filled grain and less unfilled grain than that of Sarinah. Further yield trials and resistanceof leaf blast and neck blast desease should be done to reveale the advantages of this genotype over Sarinah.Key words : Genotype, rice, productivity up landÂ Kendala utama peningkatan produksi padi nasional selama beberapa tahun terakhir antara lain adalahsulitnya mendapatkan varietas unggul baru (VUB) padi yang mempunyai potensi hasil tinggi dan adaptif denganlingkungan tumbuhnya. Pengembangan/pemasyarakatan padi varietas unggul baru (VUB) merupakan salah satuterobosan dalam upaya peningkatan produktivitas dan produksi padi serta pendapatan petani. Kegiatan pengujiangalur harapan padi sawah dataran tinggi dilaksanakan di Desa Koto Dua Lama Semurup Kecamatan Air HangatKabupaten Kerinci Provinsi Jambi pada MK 2006 dan 2007. Pengujian bertujuan untuk mendapatkan varietaspadi yang berdaya hasil tinggi dan adaptif di dataran tinggi. Pengujian dilaksanakan menggunakan RancanganAcak Kelompok dengan 3 ulangan. Pengujian ini terdiri dari 8 galur termasuk varietas pembanding Sarinah.Hasil pengujian memperlihatkan bahwa hasil tertinggi pada MK2006 dan MK 2007 berturut- pada galurRUTTST85B-5-2-2-2-0 (7,19 ton GKG /ha dan 5,80 ton GKG /ha) dan terendah pada galur BP1356-1G-KN-4(4,87 t/ha dan 4,15 t/ha GKP). Produksi galur RUTTST85B-5-2-2-2-0 6,3 â 16% lebih tinggi dari produksivarietas pembanding Sarinah (6,77 t GKP/ha dan 5 t GKP/ha). Berdasarkan data keragaan tanaman dan komponenhasil terlihat bahwa galur RUTTST85B-5-2-2-2-0 memiliki potensi produksi tinggi, tahan terhadap hama danpenyakit blas daun dan blas leher serta toleran terhadap cekaman suhu tinggi dibandingkan dengan varietas Sarinah.Kata kunci : Galur padi unggulan, produktivitas, dataran tinggi